The Role Of Arbitration In Construction Dispute Resolution: Legal Perspectives And Practices In Various Countries - Hafni Zahra Charity; Miftah Al Azrin Nainggolan; Andika Rahmad Siregar; Muhammad Rafly; Nurhanisa (ISNU Nine-Star Multidisciplinary Journal, 2024)
Arbitration is one of the alternative dispute resolution methods that is increasingly popular in the construction field, given the complexity and dynamics of construction projects that often lead to conflicts. in a business relationship or agreement, each party must be prepared to face the possibility of conflict. Disputes often arise due to differences in interpretation regarding clauses or provisions in the agreement, or other factors. Dispute resolution through the courts often leads to new problems, slow processes, high costs, and can create hostility between the parties to the dispute. Therefore, many choose out-of-court dispute resolution. This research aims to analyze the role of arbitration in construction dispute resolution, by examining the legal perspectives and practices in various countries. In the legal context, arbitration offers advantages such as time efficiency, cost, and confidentiality, as well as flexibility in the selection of arbitrators with specialized skills. Indonesian practice demonstrates various approaches and regulations that affect the effectiveness of arbitration in resolving construction disputes. The study also explores the challenges faced, such as the recognition and enforcement of arbitral awards, as well as the comparison between arbitration and litigation. As such, this study is expected to provide greater insight into the role and relevance of arbitration in resolving construction disputes in the modern era.